The Influence Factors of Regional Development to Create Regional Competitiveness : A Review - Rini Hakimi; Melinda Noer; Nofialdi Nofialdi; Hasnah Hasnah (International Journal of Agricultural Sciences, 2021)
Regional development was done before Indonesia's Independent day in 1945, but it still did not achieve the result as expected. The root cause of this problem is avoiding factors that influence regional development. The method used is an integrated review of research focused on regional development and competitiveness. This paper will discuss the external and internal factors of regional development to increase Indonesian position in regional competitiveness level. Internal factors related to regional development are management, resources, participation, local industry, infrastructure, technology, local policy, innovation, and entrepreneurship. Moreover, the external factors affecting regional development are the government, politics, market, and investment. Internal factors in regional development can be controlled; however, external factors are uncontrollable. Focusing on regional development to maintain competitive economic growth and become a competitive region should be put on innovation, entrepreneurship, and networking